# How do you solve -6(4x+1)=5-11x?

Feb 11, 2017

See the entire solution process below:

#### Explanation:

First, expand the terms in parenthesis on the left side of the equation:

$\left(- 6 \times 4 x\right) + \left(- 6 \times 1\right) = 5 - 11 x$

$- 24 x - 6 = 5 - 11 x$

Next, add $\textcolor{red}{24 x}$ and subtract $\textcolor{b l u e}{5}$ from each side of the equation to isolate the $x$ term.

$- 24 x - 6 + \textcolor{red}{24 x} - \textcolor{b l u e}{5} = 5 - 11 x + \textcolor{red}{24 x} - \textcolor{b l u e}{5}$

$- 24 x + \textcolor{red}{24 x} - 6 - \textcolor{b l u e}{5} = 5 - \textcolor{b l u e}{5} - 11 x + \textcolor{red}{24 x}$

$0 - 11 = 0 + 13 x$

$- 11 = 13 x$

Now, divide each side of the equation by $\textcolor{red}{13}$ to solve for $x$ while keeping the equation balanced:

$- \frac{11}{\textcolor{red}{13}} = \frac{13 x}{\textcolor{red}{13}}$

$- \frac{11}{13} = \frac{\textcolor{red}{\cancel{\textcolor{b l a c k}{13}}} x}{\cancel{\textcolor{red}{13}}}$

$- \frac{11}{13} = x$

$x = - \frac{11}{13}$